Who is disabled? On whether the functional definition of disability targets the same individuals as the subjective definition - Baart, Judith; Elbers, Willem; Schippers, Alice (Frontiers in Sustainability, 2023)
With the increased attention to disability as a vulnerability criterion in the Sustainable Development Goals, international organizations and NGOs within the international development sector have started to pay explicit attention to persons with disabilities, including the collection of data on persons with disabilities. The Washington Group Short Set of Questions, which focuses on functional limitations, has been gaining popularity as an assessment tool for disability. This set of questions reflects a categorization of disability that does not necessarily correspond with subjective disability assessments, such as the yes/no question (‘do you have a disability?’) which many development actors have used in their assessment tools when they collect disability data This study compares the subjective and the functional limitations assessment tools for disability to answer the question: do they identify the same individuals as persons with disabilities? Based on a survey carried out amongst persons with disabilities in Cambodia, we included both the Washington Group Short Set and a subjective question asking respondents to self-identify their disability type. We find that, although all respondents self-identified as disabled, not all respondents would be considered disabled according to the Washington Group Short Set of questions. In addition, there is little overlap between specific disability types according to a subjective classification method and the domains of functioning measured through the Washington Group methodology. Our findings affirm that categorization as abled or disabled depends on the tool used. This is important, as the assessment approach chosen by those collecting disability data can shape the design choices of policies and programs, and determine who benefits.